The Optimal Ambient Conditions for World Record and World Class Performances at the Berlin Marathon - Scheer, Volker; Valero, David; Villiger, Elias; Alvero Cruz, José Ramón; Rosemann, Thomas; Knechtle, Beat (Frontiers in Physiology, 2021)
The ‘Berlin Marathon’ is the fastest marathon racecourse in the world and has witnessed 11 world records (eight in men and three in women). Weather conditions can have an important impact on race time and we therefore examined the influence of environmental conditions (i.e., temperature, sunshine, precipitation, barometric pressure and cloud cover) on world records and elite (i.e., winner, top three and top ten finishers) marathon performances of men and women at the ‘Berlin Marathon’ between 1974 and 2019. Average world record marathon times in men were 2:03:52±0:01:19 h:min:s and 2:25:05±0:08:25 h:min:s in females (p<0.05). Male competitions were held 44 times (mean winning time: 2:09:48±0:09:15 h:min:s) and female competitions 41 times (mean winning time: 02:30:35±0:19:09 h:min:s) (p<0.05). World record performances were set at mean temperatures of 18.61±2.59°C for men and 13.07±4.01°C for women (p>0.05). The ideal environmental conditions for world record performances for men were temperatures of 18.61°C (p>0.05), sunny, mostly dry days, with higher atmospheric pressure and little cloud cover (all p>0.05). In women, ideal conditions for world records performances were temperatures of 13.07°C (p>0.05), with low atmospheric pressure (p>0.05), but significantly more rain (p<0.05), and with no sunshine (p<0.05) and cloud cover (p<0.05). With elite performances, the ideal temperatures were of 17.36±4.33°C for men and 17.93±4.07°C for women (p>0.05), with little to no rain, and moderate cloud cover and sunshine (p>0.05). In summary, novel findings are, that environmental conditions in world records performances differ between men and women, with women obtaining world records in bad weather (with rain, cloud cover and no sunshine) and men in good weather (sunny, mostly dry days, with little cloud cover). Larger sample sizes are needed to examine sex differences and environmental conditions on world record marathon performances.